2019
DOI: 10.1101/19003426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of a spatial repellent for control of malaria in Indonesia: a cluster-randomized controlled trial

Abstract: A cluster randomized, double-blinded, placebo-controlled trial was conducted to estimate protective efficacy of a spatial repellent against malaria infection at Sumba, Indonesia. Following radical cure in 1,341 children aged ≥6 months - ≤5 years in 24 clusters, households were given transfluthrin or placebo passive emanators (devices designed to release vaporized chemical). Monthly blood screening and biweekly human-landing mosquito catches were performed during 10-months baseline (June 2015 to March 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 47 publications
(55 reference statements)
0
37
0
Order By: Relevance
“…By disrupting or interfering the normal behavioral patterns of vector host-seeking and biting, the vapor-phase properties of chemicals can potentially create a spatial ‘vector-free space’ and thus reduce the risk of so-called ‘residual’ transmission as well as indoor [ 20 , 23 ]. Transfluthrin (TFT) is a relatively recent volatile AI pyrethroid that has been incorporated in a variety of commercial products (i.e., mosquito coils, aerosol sprays) and has been explored for promoting spatial repellent as a new invention class against mosquitoes [ 21 , 22 , 24 ]. Estrada et al [ 25 ] demonstrated that TFT produced the strongest spatial repellency response in Ae .…”
Section: Introductionmentioning
confidence: 99%
“…By disrupting or interfering the normal behavioral patterns of vector host-seeking and biting, the vapor-phase properties of chemicals can potentially create a spatial ‘vector-free space’ and thus reduce the risk of so-called ‘residual’ transmission as well as indoor [ 20 , 23 ]. Transfluthrin (TFT) is a relatively recent volatile AI pyrethroid that has been incorporated in a variety of commercial products (i.e., mosquito coils, aerosol sprays) and has been explored for promoting spatial repellent as a new invention class against mosquitoes [ 21 , 22 , 24 ]. Estrada et al [ 25 ] demonstrated that TFT produced the strongest spatial repellency response in Ae .…”
Section: Introductionmentioning
confidence: 99%
“…Although this study suggests that EPTI reduces human landing rate for both mosquitoes, additional evidence is needed to determine whether resistance in mosquitoes is detrimental to the e cacy of trans uthrin. This is particularly important in areas where trans uthrin will be considered for the control of mosquito vectors [20].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that VPs such as trans uthrin and meto uthrin are effective at reducing the human landing rate (HLR) of a range of mosquitoes [16]. Passive emanators treated with trans uthrin or meto uthrin consistently demonstrated personal protective e cacy exceeding 50% in studies conducted in Cambodia [17], Tanzania [18], Belize [19] and Indonesia [20]. Trans uthrin applied to hessian strips as eave-positioned targeted insecticide (EPTI) has provided over 68% reduction in human vector contact in semi-eld studies [10,21] and over 80% in eld studies in Tanzania [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…These data emphasize the need for new tools, such as spatial [ 51 ] or topical repellents, as well as new research that evaluates novel paradigms directed at residual transmission occurring outside the functional scope of present interventions, accelerating progress towards elimination.…”
Section: Discussionmentioning
confidence: 95%